Introduction to inertial confinement fusion - Pfalzner, S. (New York: Taylor and Francis, 2006)
Newcomers to the field of inertial confinement fusion (ICF) often have difficulty establishing a clear picture of the overall field. The reason for this is because, while there are many books devoted to special topics within the field, there is none that provides an overview of the field as a whole. An Introduction to Inertial Confinement Fusion fills this gap with an overview of the processes involved in ICF presented at an accessible level. After a broad overview, the book follows the processes from the driver technology to burn physics in chronological order. As each topic appears, the author details the physical concepts and obstacles. The book concludes with a look to the future prospects of the field.
Appendices A-B, 211-218p.; Bibliographical references 219-227p.; Index 228-232p.
Keywords: Inertial confinement fusion; Nuclear Fusion; Nuclear Physics; Plasma Physics; Pallet Fusion